The African union’s policy coherence approach for good governance - Hamouda, Sara (University of the Witwatersrand, Johannesburg, 2022)
During the past decade, concern for promoting good governance has emerged as an imperative engine for socio-economic and political transformation on the African continent, especially with the adoption of Agenda 2030 for Sustainable Development and Agenda 2063: The Africa We Want. However, progress towards this aspiration re- mains sluggish despite many international and regional efforts to galvanize improvements in governance. This exploratory research examines how fit for purpose the institutional arrangements and coordination mechanisms of the African Union Commission, African Peer Review Mechanism and AU Development Agency AUDA-NEPAD are, to ensure policy coherence for achieving this goal, notably through the implementation, monitoring and evaluation of Agenda 2063, Aspiration 3 (good governance). One of the main findings of the research is that there is a lack of vertical and horizontal coherence between the three organs to ensure policy coherence and integration for advancing good governance programmes alongside monitoring and evaluation mechanisms for their performance, accountability, and delivery. Another finding speaks to the necessity of enhancing political ownership and commitment of AU member-states
A research report submitted to the Faculty of Management, University of the Witwatersrand, in 50% fulfillment of the Requirement for Masters in Management, Johannesburg 2022
Keywords: African Union; Policy Coherence; Good Governance; Agenda 2063; UCTD; SDG-17: Partnerships for the goals